Palladium-catalyzed substitution of allylic alcohols with sulfinate salts: A synthesis of bicalutamide. (8th June 2021) - Jhang, Yin-Jia; Chang, Chieh-Yu; Lin, Yu-Huan; Lee, Chein-Chung; Wu, Yen-Ku
Graphical abstract: Highlights: In situ activation of allyl alcohols with Ti(IV) alkoxide and palladium catalysis. Phenylboronic acid displays a favorable additive effect in the title reaction. A concise, four-step conversion of methallyl alcohol to bicalutamide is described. Abstract: A method is presented for the direct substitution of allylic alcohols with sodium arylsulfinates. The process involves a cooperative action of palladium catalysts, phenylboronic acid and titanium tetraisopropoxide. By taking advantage of this protocol, we achieved a concise synthesis of bicalutamide, an anti-androgen compound for treating prostate cancer.